A Discussion of the Use of Virtual Reality for Training Healthcare Practitioners to Recognize Child Protection Issues - Drewett, Olivia; Hann, Gayle; Gillies, Marco; Sher, Carmel; Delacroix, Sylvie; Pan, Xueni; Collingwoode-Williams, Tara; Fertleman, Caroline (Frontiers in Public Health, 2019)
Background Virtual reality technology is a rapidly developing tool which has been shown to have exciting prospects in the field of medical education (Pan et al., 2016). In a recent, subsequent study, Pan et al. consider the potential of the same technology in the realm of child protection training and safeguarding issues (Pan et al., 2018). To build upon the Pan et al., 2018 study, a panel discussion was held at The Centre for Behaviour Change Annual Conference 2018 to discuss the question “Can a virtual reality communication scenario be used to teach General Practitioners and trainees how to recognise and manage child protection issues?”. Methodology The above study comprised an immersive virtual reality consultation, in which the ability of 63 doctors to pick up covert safeguarding cues was tested in the context of a consultation with an adult patient, where the patient’s child happened to be present as well. The study and its findings were discussed at the Centre for Behaviour Change 4th Annual Conference, and this paper summarises the opinions of both the panel and the audience. Viewpoint Safeguarding is a challenging area of practice where we must listen to the child, and tackle difficult conversations with parents. Within medical training, role play is the gold standard for teaching how to communicate in difficult scenarios. Given the ethical questions surrounding children being asked to role play such abuse, the use of virtual reality characters could have a key role in upgrading current practices in medical education on safeguarding.